اقتراح المتطلبات اللازمة لتطوير التنظيم العقاري وإدارته في بلديات الأرياف، تطبيق على ريف مدينة اللاذقية - زوباري علي; يحيى منير; شعبان فادي; حويجه روز (Latakia University Journal -Engineering Sciences Series, 2019)
This research aims to propose the requirements that needed for developing the cadastral regulation and management in Lattakia’s rural municipalities, in order to support sustainable land development, and protect the cadastral properties, as a fundamental step towards a cadastral system development. We conducted an analytical study in some rural municipalities (Mashqieta) and at the cadastral directorate. It included the master plan, building control regulation, subdivision projects. The strengths of the current cadastral regulation have been identified: its reliability, the existence of master plans, and building control regulation in all the municipalities. Weaknesses were also identified in terms of: master plan that did not take into account the boundaries of the properties, the land topography, the criteria weakness of selection the organizational segments, the building control regulation, and weakness of the cadastral and regulatory legislation. Many requirements have been proposed for developing the cadastral regulation in rural municipalities, such as: legal, technical, institutional, and other requirements related to functions, jobs, experiences and qualifications. يهدف هذا البحث إلى اقتراح متطلبات تطوير تنظيم العقارات وإدارتها في بلديات الأرياف، بما يخدم تنفيذ أعمال التنظيم والتقسيم العقاري، لدعم التنمية المستدامة للأراضي، وحماية الملكيات العقارية، كخطوة أولية وأساسية على طريق التطوير العقاري. لتحقيق هذا الهدف أجرينا دراسة ميدانية تحليلية في بلدية اللاذقية، وبعض بلديات الريف (بلدية مشقيتا)، بالإضافة لمديرية المصالح العقارية، شملت المخطط التنظيمي، ونظام ضابطة البناء، ومشاريع التقسيم العقارية، وإشكالياتها، وتأثيرها على الأملاك الخاصة والعامة وعلى تنظيم المناطق. نتيجةً لهذه الدراسة، تم تحديد نقاط القوة في التنظيم العقاري الحالي؛ وهي: موثوقية التسجيل العقاري، ووجود مخططات تنظيمية وأنظمة بناء في كل البلديات. كما تم حصر نقاط الضعف؛ من حيث: المخطط التنظيمي الذي لم يُراعَ به حدود الملكيات العقارية، وطبوغرافية الأرض، بالإضافة لضعف معايير اختيار الشرائح التنظيمية، ونظام ضابطة البناء، وضعف التشريعات التنظيمية والعقارية. تم التوصل إلى مجموعة من المتطلبات لتطوير تنظيم العقارات وإدارتها في بلديات الأرياف؛ وهي: المتطلبات القانونية، والمتطلبات التقنية، والمتطلبات المؤسساتية، ومتطلبات المهام والوظائف، بالإضافة لمتطلبات الكفاءات والخبرات.